Cross-cultural adaptation of the EMIC Stigma Scale for people with leprosy in Brazil - Fabiane Frota da Rocha Morgado; Erika Maria Kopp Xavier da Silveira; Anna Maria Sales; Lilian Pinheiro Rodrigues do Nascimento; Euzenir Nunes Sarno; José Augusto da Costa Nery; Aldair J Oliveira; Ximena Illarramendi (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE Describe the process of cross-cultural adaptation of the "Explanatory Model Interview Catalog - Stigma Scale" for people affected by leprosy in Brazil. METHODS After being authorized by the author of the scale to use it in the national context, we initiated the five steps process of cross-cultural adaptation: (1) translation, (2) synthesis meeting, (3) back-translation, (4) committee of experts and (5) pre-test. The internal consistency of the scale was evaluated using Cronbach's alpha coefficient. RESULTS The 15 items of the scale's original version were translated into Brazilian Portuguese. The adapted scale showed evidence of a good understanding of its content, attested both by experts and members of the target population. Its internal consistency was 0.64. CONCLUSIONS The adapted instrument shows satisfactory internal consistency. It may be useful in future studies that intend to provide broad situational analysis that supports solid public health programs with a focus on effective stigma reduction. In a later study, the construct's validity, criterion, and reproducibility will be evaluated.